'I ate too much so I must have been sad': Emotions as a confabulated reason for overeating. (1st August 2016) - Adriaanse, Marieke A.; Prinsen, Sosja; de Witt Huberts, Jessie C.; de Ridder, Denise T.D.; Evers, Catharine
Abstract: Background: Emotional eating (i.e., overeating in response to negative affect) is a commonly accepted explanation for eating behaviors that are not in line with personal eating-norms. However, the empirical evidence for a causal link between self-reported emotional eating and overeating is mixed. The present study tested an alternative hypothesis stating that high emotional eating scores are indicative of a susceptibility to use negative affect as a confabulated, post-hoc reason to explain overeating. Methods: Female students ( N  = 46) participated in a 'taste-test' and came back to the lab a day later to receive feedback that they either ate too much (norm-violation condition) or an acceptable amount of food (control condition), whereafter emotional eating was assessed. Negative affect was measured several times throughout the study. Results: In the norm-violation condition, participants with high emotional eating scores retrospectively rated their affect prior to eating as more negative than participants with low emotional eating scores. In the control condition, no effect of emotional score on affect ratings was found. Discussion: For some individuals emotional eating scores may represent a tendency to retrospectively attribute overeating to negative affect. This could explain the lack of consistent findings for a link between self-reported emotional eating and overeating.